Combined effect of synthetic enterocin CRL35 with cell wall, membrane-acting antibiotics and muranolytic enzymes against Listeria cells - Salvucci, Emiliano Jesus (2010)
Aims: To evaluate the inhibition effectiveness of enterocin CRL35 in combination with cell wall, membrane-acting antibiotics and muranolytic enzymes against the foodborne pathogen Listeria.Methods and Results: Synthetic enterocin CRL35 alone and in combination with monensin, bacitracin, gramicidin, mutanolysin and lysozyme were used in this study. Minimal inhibitory concentration (MIC) and fractional inhibitory concentration (FIC) index assays were performed using Listeria innocua 7 and Listeria monocytogenes FBUNT as sensitive strains. Antibiotics showed positive interactions with the bacteriocin in both strains tested. On the other hand, when mutanolysin and enterocin CRL35 were added to resting cells in a buffer system, the lytic effect of mutanolysin was enhanced. However, the addition of mutanolysin showed no effect on the growth of L. innocua 7 cells in a culture medium. Moreover, mutanolysin allowed the overgrowth of L. innocua 7 cells to an OD similar to control cells in the presence of inhibitory concentration of enterocin CRL35. In contrast, the combination of lysozyme and enterocin CRL35 resulted in a 50% inhibition of the L. innocua 7 growth.Conclusions: Based on our results, we conclude that the combination of synthetic enterocin CRL35 with some antibiotics is effective against L. innocua 7 and L. monocytogenes FBUNT cells, and more importantly the amount of these agents to be used was considerably reduced. The effectiveness of the combination of synthetic enterocin CRL35 with muramidases seems to depend on complex environments, and more detailed studies need to be performed to elucidate this issue.Significance and Impact of the Study: Enterocin CRL35 represents a promising agent that not only can ensure the quality and safety of food but it can also be combined with several antimicrobial agents important in the medical field.